2021
DOI: 10.3949/ccjm.88a.20183
|View full text |Cite
|
Sign up to set email alerts
|

Chest pain: The importance of serial ECGs

Abstract: Chest pain: The importance of serial ECGsA 44-year-old man, previously well, presented to the emergency department with severe hypertension and a 4-hour history of typical angina-like chest pain with associated diaphoresis. He had dyslipidemia, a 5-pack-year history of smoking, and, likely, undiagnosed hypertension.On arrival, his blood pressure was 200/110 mm Hg, representing a hypertensive emergency. A clinical examination was unremarkable. A blood sample was sent for troponin analysis, and a nitroglycerin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…6 Repeat ECG acquisition in the presence of new symptoms or ongoing, severe chest pain can be performed quickly and has the potential to identify a developing STEMI without needing to wait for lab values to result. 7 With an initial normal or nondiagnostic ECG, hospitalists often repeat the ECG one or more times during the hospitalization. The 2010 American Heart Association guidelines on the management of low-risk patients with chest pain recommended repeating the ECG at 5-to 10-min intervals, although it did not specify the ideal duration of monitoring.…”
Section: Why You Might Think Routine Serial Ecgs Are Helpful In Evalu...mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Repeat ECG acquisition in the presence of new symptoms or ongoing, severe chest pain can be performed quickly and has the potential to identify a developing STEMI without needing to wait for lab values to result. 7 With an initial normal or nondiagnostic ECG, hospitalists often repeat the ECG one or more times during the hospitalization. The 2010 American Heart Association guidelines on the management of low-risk patients with chest pain recommended repeating the ECG at 5-to 10-min intervals, although it did not specify the ideal duration of monitoring.…”
Section: Why You Might Think Routine Serial Ecgs Are Helpful In Evalu...mentioning
confidence: 99%
“…Another study from 2000 found that serial ECGs resulted in changes to therapy in 15% of high‐risk chest pain patients after an initial nondiagnostic evaluation 6 . Repeat ECG acquisition in the presence of new symptoms or ongoing, severe chest pain can be performed quickly and has the potential to identify a developing STEMI without needing to wait for lab values to result 7 …”
Section: Why You Might Think Routine Serial Ecgs Are Helpful In Evalu...mentioning
confidence: 99%